La desigualdad cultural en cuestión (con una ilustración en Basura de Hector Abad Faciolince) - Ilian, Ilinca (Verbum – Analecta Neolatina, 2021)
This article proposes a reflection on the theme of cultural inequality, studied in the field of sociology by Bourdieu, which we will try to link with the debates about the criteria of distinction between “good” and “bad” literature. In the first instance we will talk about the aporia to which the policies of the decades between 1970–2000 aimed at cultural democratization led, making use of the studies carried out by Modesto Gayo in several Spanish-speaking countries. We will then refer to the mutual interfusion between the cultural field and the market as well as the destabilizing effect on the literary canon caused by the culturalist and deconstructivist paradigm in literary criticism. We will briefly call into question the capacity of the Internet to produce real cultural equality and finally analyze the novel Basura (2000) by the Colombian writer Héctor Abad Faciolince as a literary reflection on the value of literature in the world today.